Oxidized Phospholipids and Neutrophil Elastase Coordinately Play Critical Roles in NET Formation - Tokuhiro, Takuto; Ishikawa, Akane; Sato, Haruka; Takita, Shunya; Yoshikawa, Ayuri; Anzai, Ryoko; Sato, Shinichi; Aoyagi, Ryohei; Arita, Makoto; Shibuya, Takumi; Aratani, Yasuaki; Shimizu, Shigeomi; et al. (Frontiers in Cell and Developmental Biology, 2021)
Neutrophil extracellular traps (NETs) are web-like structures consisting of decondensed chromatin DNA and contents of granules, such as myeloperoxidase (MPO) and neutrophil elastase (NE). NETs are usually released from neutrophils undergoing NETosis, a neutrophil-specific cell death mode characterized by the collapse and disappearance of cell membranes and nuclear envelopes. It is well known that production of reactive oxygen species (ROS) triggers NETosis and NET formation. However, details of intracellular signaling downstream of ROS production during NETosis and NET formation remains uncertain. Here, we demonstrated that the peroxidation of phospholipids plays a critical role in NETosis and NET formation induced by phorbol 12-myristate13-acetate (PMA) or immune complex in vitro and by lipopolysaccharide (LPS) in vivo. This phospholipid peroxidation is mediated by the enzymatic activity of MPO. On the other hand, NE, which was previously reported to be released from granules to cytosol by MPO during NET formation, is not required for either the peroxidation of phospholipids or the execution of NETosis, but contributes to chromatin decondensation and nuclear swelling independently of MPO-mediated oxidized phospholipids. Analysis of isolated nuclei clearly demonstrated that oxidized phospholipids and NE differently yet synergistically execute chromatin decondensation and nuclear swelling, and the subsequent release of nuclear contents. These findings indicate the dual roles of MPO in NETosis and NET formation, and provide new insight into the molecular mechanism of these phenomena.